Spices in a Product Affect Emotions: A Study with an Extruded Snack Product - Bell, Brandon; Adhikari, Koushik; Chambers, Edgar, IV; Alavi, Sajid; King, Silvia; Haub, Mark (My University, 2017)
Food commonly is associated with emotion. The study was designed to determine if a spice blend (cinnamon, ginger, nutmeg, and cloves) high in antioxidants can evoke changes in consumer emotions. This was an exploratory study to determine the effects of these four spices on emotions. Three extruded, dry snack products containing 0, 4, or a 5% spice blend were tested. One day of hedonic and just-about-right evaluations (n = 100), followed by three days of emotion testing were conducted. A human clinical trial (n = 10), using the control and the 4% samples, measured total antioxidant capacity and blood glucose levels. The emotion “Satisfied” increased significantly in the 5% blend, showing an effect of a higher spice content. The 4% blend was significantly higher in total antioxidant capacity than the baseline, but blood glucose levels were not significantly different.
Citation: Bell, B., Adhikari, K., Chambers, E., Alavi, S., King, S., & Haub, M. (2017). Spices in a Product Affect Emotions: A Study with an Extruded Snack Product †. Foods, 6(8), 70. https://doi.org/10.3390/foods6080070
Keywords: Antioxidants; Clinical; Emotion; Extruded Snack; Overall Liking; Spices